73.4k views
0 votes
I need help with 1 & 3.. thanks

I need help with 1 & 3.. thanks-example-1
User Thalador
by
5.2k points

1 Answer

2 votes

Answer:

y/x = (a + b) / (m + n)

Explanation:

-(xb − ym) = -yn + xa

Distribute:

-xb + ym = -yn + xa

Combine like terms:

ym + yn = xa + xb

Factor:

y (m + n) = x (a + b)

Rearrange:

y/x = (a + b) / (m + n)

User BabyishTank
by
4.8k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.